Assessing The Students’ Prospective Perceptions Of The Final Master Project In Actuarial Science - Mayorga-Toledano, María Cruz; Trigo-Martínez, Eduardo; Fernández-Morales, Antonio (My University, 2022)
The final master project plays a key role in the curriculum design of the Actuarial Science Master degree at the University of Málaga. Students have to fulfil their projects at the end of the two-years study program in order to get the master’s degree. The nature of the projects requires the combination of a wide range of skills, which includes analytical and technical ones, as well as professional and soft skills. From this point of view, completing a final master project in this study program can become an interesting opportunity to experiment with real tasks of the actuarial profession before entering the labour market. Furthermore, the Actuarial Science Master degree at the University of Málaga offers the possibility of including a working actuary as a second supervisor, besides the academic one. Simulating or working with real problems in the field of Actuarial Science in the final master project, which use to be complex in nature and often multidisciplinary, also constitutes a useful way to integrate the contents of the different courses of the study program and get them in context. However, the quick transition of our students to the professional market, mainly through the internships, sometimes becomes a hurdle to properly finish the final projects in the scheduled academic calendar. In an attempt to improve the satisfaction and success rates, a group of lecturers are conducting a broad study about the final master project in Actuarial Science, that includes subjective aspects.
Keywords: Riesgo (Seguro); Actuarial; Final project; Professional skills